Pengaruh Citra Merek (Brand Image) dan Kualitas Produk Terhadap Keputusan Pembelian Produk Scarlett Whitening Pada Mahasiswa Fakultas Ekonomi Universitas Pendidikan Ganesha - Rumanis, Anita; Suwendra, I Wayan (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2024)
This study aims to determine the effect of brand image variables and product quality on purchasing decisions for Scarlett Whitening products for students of the Faculty of Economics, Ganesha University of Education. The population in this study were all undergraduate and D4 students of the Faculty of Economics. The number of samples used in this study was 100 using the Slovin formula. The sampling technique used was purposive sampling technique. The data collection method uses a questionnaire with the data analysis method, namely multiple linear regression analysis. Hypothesis testing using the t test and F test processed with the help of SPSS 26 for Windows. The results of this study suggest that: (1) Brand image has a positive and significant effect on purchasing decisions for scarlett whitening products with a t value above the t table value, namely 8.149> t table value 1.984 and a significance value of 0.000<0.05 (2) Product quality has a positive and significant effect on purchasing decisions for scarlett whitening products with a t value above the t table value, namely 7, 770> t table value 1.984 and a significance value of 0.000 <0.05 and (3) Brand image and product quality have a positive and significant effect on purchasing decisions for scarlett whitening products with a calculated F value greater than the F table, namely the calculated F value of 44.386> F table 3.09 and a significance value of 0.000 <0.05.